Isotope fractionation and isotope decoupling during anammox and denitrification in marine sediments. (15th December 2015) - Dähnke, Kirstin; Thamdrup, Bo
Abstract: To evaluate the relation of isotope fractionation during sedimentary nitrate reduction with sediment reactivity, we measured nitrate and nitrite reduction rates and corresponding isotope changes in marine sediments in the Skagerrak. Our sampling sites encompassed a gradient of reactivity, oxygen consumption, and manganese concentration. Anammox was the main N2 ‐production pathway at the deepest site. For this site, we calculated the intrinsic isotope effect of nitrite consumption by anammox in marine sediments, and found that it is ∼ −20‰, in accordance with culture studies. Denitrification was dominant at shallower sites, which confirms previous studies from whole core incubations. The N‐isotope effect of denitrification, 15 ε, ranged from −12‰ to −16‰. Oxygen isotopes of nitrate were more variable, and the ratio of 18 ε / 15 ε, was highly variable in all sediments we investigated. At all stations, the oxygen isotope effect was (partly or entirely) decoupled from the nitrogen isotope effect. In denitrification‐dominated sediments, this decoupling of oxygen and nitrogen isotopes appeared to be driven by nitrite reoxidation in anoxic sediment incubations, either due to enzymatic reversibility of the respiratory nitrate reductase Nar, or to reversibility on the community level. In anammox‐dominated sediments, this effect was also evident in N‐isotope changes, likely due to net nitrate production and isotope exchange that is promoted by anammox. These findings suggest that the ratio of 18 ε / 15 ε in marine environments is more flexible than previously assumed, because enzymatic or community‐driven isotope exchange can alter both N and O isotopes, deviating from standard Rayleigh‐type fractionation.